Diagnoza i ochrona dziecka z traumą rozwojową w polskim systemie oświatowym - Joanna Helios; Wioletta Jedlecka (Problemy Wczesnej Edukacji)
The aim of this article is to diagnose the symptoms of disorders and functioning of children at risk and traumatic development in the Polish educational system, as well as to identify possible legislative solutions related to appropriate educational and therapeutic activities and to safeguard the educational rights of these children. In educational law, there are legal solutions that provide the opportunity to organize for a child with more favorable conditions in the education system based on the value of educational equality.